Comparison of pregnancy specific protein-b in abortive and pregnant ewes - Saat, Nevzat; Cetinkaya, Yusuf Bilal; Ozturk, Tunahan; Ozturk, Buse; Risvanli, Ali (Massimo Morgante, 2025)
This study aimed to investigate serum Pregnancy-Specific Protein B (PSPB) levels in pregnant and aborting ewes to evaluate its potential as a biomarker for pregnancy health and pregnancy loss in small ruminants. Additionally, the study examined whether PSPB concentrations differ in ewes that experienced abortion due to various bacterial agents (Brucella spp., Salmonella spp., and Campylobacter spp.). A total of 88 Akkaraman ewes were included in the study, comprising 29 pregnant and 59 aborting animals. The causes of abortion were confirmed microbiologically, and blood samples were collected from pregnant ewes on gestational days 28-30, and from aborting ewes approximately 10 days post-abortion. Serum PSPB levels were measured using a sheepspecific Enzyme-Linked ImmunoSorbent Assay (ELISA) assay. Chi-square test and one-way ANOVA test were used to evaluate the data. PSPB concentrations in pregnant ewes (19.13 ± 2.36 ng/mL) were significantly higher than those in aborting ewes (13.50 ± 0.66 ng/mL). Among aborting ewes, mean PSPB levels were 13.81 ± 1.40 ng/mL for Salmonella spp., 13.82 ± 2.17 ng/mL for Campylobacter spp., and 14.61 ± 1.60 ng/mL for Brucella spp.; however, no statistically significant differences were observed between the bacterial agents. The reduction in PSPB concentrations following abortion supports previous studies indicating that low PSPB or Pregnancy-Associated Glycoprotein (PAG) levels are associated with embryonic or fetal loss. These findings demonstrate that PSPB, which enters the maternal circulation around day 21 of gestation, is a reliable marker not only for pregnancy detection but also for predicting pregnancy loss. The lack of variation in PSPB levels according to the type of bacterial infection highlights its direct value in assessing abortion events. Overall, the results suggest that PSPB has potential as a standard biomarker for monitoring pregnancy health and the early detection of pregnancy loss in sheep. Advanced studies involving larger sample sizes and longitudinal monitoring are warranted to further validate the accuracy and reliability of PSPB in clinical applications. © 2025, Massimo Morgante. All rights reserved.
Keywords: Abortion; Bacterial agent; Ewe; Pregnancy specific protein b